2007
DOI: 10.1111/j.1468-0475.2007.00134.x
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Capital and Venture Capital Investments: New Evidence from European Panel Data

Abstract: Countries with a high amount of knowledge capital are likely to have higher volumes of venture capital (VC) investments because more researchers come up with innovative business ideas that require venture capital finance. Using panel data techniques, the paper finds evidence that VC investments depend strongly on the countries' knowledge capital measured by the number of patents, or the number of R&D researchers, or gross domestic expenditures on R&D. In addition, the paper analyzes whether government-financed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 42 publications
4
27
1
1
Order By: Relevance
“…Employing the panel unit root tests developed by Levin et al (2002), which assumes identical coefficients of the lagged endogenous variable across countries, and the test developed by Im et al (2003), which allows heterogeneous coefficients of the lagged endogenous variables across countries, Schertler (2005b) has shown that the hypothesis of non-stationarity for the volume of various types of private equity investments relative to GDP or the number of various types of private equity investments relative to the population cannot be rejected. Therefore, levels of private equity investments relative to GDP are not stationary, while first differences of investments relative to GDP and the percentage changes in investments are stationary.…”
Section: Empirical Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…Employing the panel unit root tests developed by Levin et al (2002), which assumes identical coefficients of the lagged endogenous variable across countries, and the test developed by Im et al (2003), which allows heterogeneous coefficients of the lagged endogenous variables across countries, Schertler (2005b) has shown that the hypothesis of non-stationarity for the volume of various types of private equity investments relative to GDP or the number of various types of private equity investments relative to the population cannot be rejected. Therefore, levels of private equity investments relative to GDP are not stationary, while first differences of investments relative to GDP and the percentage changes in investments are stationary.…”
Section: Empirical Modelmentioning
confidence: 99%
“…In order to capture developments in stock market segments for fast-growing firms, I created a variable of annual stock market returns calculated from daily return indexes of Europe's stock markets for fast-growing firms (see also Schertler 2005b). For Germany I used the share index of the Neuer Markt founded in 1997, for France I used the share index of the Nouveau Marché founded in 1996, for Spain I used the share index of the Nuevo Mercado founded in 2000, and for the United Kingdom I used the share index of the Alternative Investment Market founded in 1995.…”
Section: Financial Intermediation and Financial Marketsmentioning
confidence: 99%
See 2 more Smart Citations
“…Different measures of patenting activity, such as patent count, patent families, and so on, were discussed next (cf. Hand, 2005;Schertler, 2007;Conti et al, 2011;Munari & Toschi, 2008). We hoped thereby to discover whether patenting would affect the size of the investment, and so opened this up for debate (Cockburn & MacGarvie, 2009;Mann & Sager, 2007;Baum & Silverman, 2004).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%